2001
DOI: 10.1023/a:1017950425012
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The human mesonephros is currently regarded as a simplified version of the foetal metanephros, primarily due to the close morphological resemblance between these two structures. The aim of the present study was to define whether human mesonephric and foetal metanephric nephrons share immunophenotypical traits in their corresponding structures (glomeruli, proximal and distal tubules). For this purpose we first investigated immunohistochemically the overall expression and topographical distribution of cytokerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…In addition, α-SMA exhibited an increasingly mesangial expression, paralleling the morphological maturation of the metanephric glomerulus (Magro et al, 2001).…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations
“…In addition, α-SMA exhibited an increasingly mesangial expression, paralleling the morphological maturation of the metanephric glomerulus (Magro et al, 2001).…”
Section: Introductionmentioning
confidence: 85%
“…The schematic classification of metanephrogenesis in camel embryos is divided into four stages, based on the characteristic features of each developmental stage previously reported by Osman et al (2014). The present work investigates the immuno‐localization of some significant proteins such as α‐SMA, as a cytoskeleton marker (Alpers et al, 1992; Oliver and Awqati 2000; Naruse et al, 2000 and Magro et al, 2001); CD34, as an endothelial marker (Naruse et al, 2000); Osteopontin, an important factor in tubulogenesis (Xie et al, 2001); and E‐cadherin, as cell–cell adhesion molecule (Cho et al, 1998; Ulf et al, 2002; Terada et al, 2017). The analysis revealed that all the proteins examined were detected as either membranous or cytoplasmic proteins.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations